Heat Transfer Analysis of 3-D Viscoelastic Nanofluid Flow Over a Convectively Heated Porous Riga Plate with Cattaneo-Christov Double Flux - Loganathan, K.; Alessa, Nazek; Kayikci, Safak (Frontiers in Physics, 2021)
The impact of heat absorbing viscoelastic nanofluidic (VENF) flow along a convectively heated porous Riga plate (PRP) with Cattaneo-Christov double flux (CCDF) was analytically investigated. The nanofluidic model was implemented with the diversity of Brownian motion (BM) and thermophoresis. Making use of the transformations provided, the PDE systems are altered into an ODE systems. We use of homotopy analysis method to solve these systems analytically. The reaction of the apposite parameters on fluid velocity, fluid temperature, nanoparticle volume fraction (NPVF), skin friction coefficients (SFC), local Nusselt number (LNN) and local Sherwood number (LSN) are shown with vividly explicit details. It is found that the fluid velocities reflect a declining nature for the development of viscoelastic and porosity parameters. The fluid heat becomes rich when the escalating the radiation parameter. In addition, the nanoparticle volume fraction displays a declining nature towards the higher amount of thermophoresis parameter whereas the reverse trends was gotten for Brownian motion parameter. We also found the fluid temperature is high in viscoelastic nanofluid compared to the viscous nanofluid. We change the fluid nature from heat absorption to heat generation, the fluid temperature also rises. In addition, the fluid heat becomes suppresses when we change the flow medium from stationary plate (SP) to Riga plate (RP) for heat absorption/generation cases. Theses analyzes are very useful in thermal engineer for designing the thermal systems.